Erfassung von Pruritus - aktuelle Standards und Implikationen für die Praxis: Konsensuspaper der Initiative Pruritusparameter der Arbeitsgemeinschaft Pruritusforschung (AGP) - Ständer, Sonja; Weisshaar, Elke (Der Hautarzt, 2012)
With a prevalence of 20%, chronic pruritus is a symptom of many diseases with major impact on healthcare costs. The lack of specific therapeutic measures makes the development of new drugs and their testing in clinical trials urgent. It is not possible to measure pruritus in an objective way. For these reasons, it is necessary to have a series of standardized measures to characterize pruritus in a reliable way. Intensity scales such as the visual analog scale (VAS) are most frequently used to document the course of the symptoms. However, for assessing pruritus intensity, VAS is not an optimal instrument, although it cannot be dispensed with. The VAS should be combined with other scales in clinical studies in order to internally test the consistency of data. Other instruments for assessing intensity and course of pruritus are in the process of development. Presently scratch activity and scratch-associated lesions can be documented in a descriptive fashion. There are some studies that have employed devices to document scratch activity; however, methodological studies are not yet available. The patient-benefit index is an indispensable tool in clinical trials. A questionnaire for gathering data on the history and some pruritus-specific parameters has been developed and published. Questionnaires on patient quality of life, anxiety and depression are helpful in obtaining data on other cost-relevant parameters. A questionnaire on the quality of life, for instance, can provide important help in the assessment of the burden of the disease. The results of these questionnaires can be correlated with data on pruritus intensity scales. The relevant questionnaires have been partially digitalized so that they are available immediately as part of patient care. Additional methodological developments and studies are required in order to define a robust set of instruments for measuring pruritus in daily practice and in clinical studies.
Gesehen am 09.08.2018